2016
DOI: 10.1177/0269216315626353
|View full text |Cite
|
Sign up to set email alerts
|

Hospice assist at home: does the integration of hospice care in primary healthcare support patients to die in their preferred location – A retrospective cross-sectional evaluation study

Abstract: Hospice assist at home service supports patients to die in their preferred place of death. Shared responsibility of proactive care in primary care collaboration enabled patients to express preferences. Hospice care should focus on local teamwork, to contribute to shared responsibilities in providing optimal palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
0
22
2
4
Order By: Relevance
“…Two quantitative non experimental studies using a retrospective cross -sectional design evaluated hospice palliative care programmes at home or at a community level in both Netherlands and Singapore. [12,13] The final two studies were mixed methods. One of which Downing et al [14] evaluated three hospice palliative care models in Kenya and Malawi while Jack et al [15] study examined hospice at home services model based on the experience of health care professional in their delivery of services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two quantitative non experimental studies using a retrospective cross -sectional design evaluated hospice palliative care programmes at home or at a community level in both Netherlands and Singapore. [12,13] The final two studies were mixed methods. One of which Downing et al [14] evaluated three hospice palliative care models in Kenya and Malawi while Jack et al [15] study examined hospice at home services model based on the experience of health care professional in their delivery of services.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] Nine of the reviewed articles showed that models of hospice at home care utilizes a holistic approach to providing end of life care for patients with terminal illness and their significant others. [7][8][9][10][11][12][13][14][15] These articles also revealed that healthcare providers provide multidimensional care, such as physical, psychological, social, and bereavement support for patients and families in order to decrease suffering. They also went on to say that the models of hospice at home care provided physical support through managing disease symptoms such as pain.…”
Section: Multidimensional Carementioning
confidence: 99%
“…The hospice centred-group is the exception, as GPs are not the driving force of this group and join only incidentally when invited by the hospice team, and the group meets fortnightly. This group runs by a different model, hospice care at home (HaHo), which incorporated the element of recurrent meetings from the PaTz-model as the second of four components [23]. The first component is a GP requested home visit to a patient from a hospice nurse consultant (HNC), who performs a multidimensional assessment, develops a care plan and provides specialist support to patients and relatives.…”
Section: Reflections On the Application Of The Basic Principles Of Patzmentioning
confidence: 99%
“…The first component is a GP requested home visit to a patient from a hospice nurse consultant (HNC), who performs a multidimensional assessment, develops a care plan and provides specialist support to patients and relatives. The third and fourth component are telephone backup provided by the hospice and the assignment of one coordinator of care respectively [23]. As a lack of time is considered the most important barrier to participate in a regular PaTz-group [18], the higher meeting frequency may explain the practical absence of GPs in this group.…”
Section: Reflections On the Application Of The Basic Principles Of Patzmentioning
confidence: 99%
“…They include pharmacological treatment, treatment of somatic symptoms and pain treatment, as well as psychological care, rehabilitation, free rental of medical and auxiliary equipment [1]. An important goal of hospice care is to improve the quality of life of patients and their families [2,3]. A decrease in functional efficiency is considered to be an important indicator of quality of life [4].…”
mentioning
confidence: 99%